Development, Characterization and Cross-species Transferability of Expressed Sequence Tag-simple Sequence Repeat (EST-SSR) Markers Derived from Kelampayan Tree Transcriptome - S.L., Lai,; P.S.,, Ho; W.S., Pang (Asian Network for Scientific Information, 2013)
Neolamarckia cadamba (or locally known as kelampayan) is an important fast growing plantation tree species that confers various advantages for timber industry as a strategy for reducing the logging pressure on natural forests for wood production to an acceptable level. Hence, attempts were made to develop a set of EST-SSR markers for kelampayan trees based on the EST sequences of kelampayan (NcdbEST) and further assessed the polymorphisms and transferability of the markers to other species. In this study, 155 (2.34%) out of 6,622 EST sequences which contain 232 SSRs were mined from NcdbEST. Of these, 97 ESTs were assigned with putative functions and gene ontology terms. Eighteen EST-SSR markers were developed according to the criteria, and further characterized and validated by using 50 individuals of kelampayan from two selected mother trees. The markers exhibited a considerable high level of polymorphism in kelampayan trees with an average of 4.17 and 4.11 alleles per locus, and PIC values of 0.465 and 0.537, respectively for mother trees T1 and T2. Parentage assignment analysis suggests a high probability for kelampayan trees to be predominantly outcrossed. The transferability rate was ranging from 16.7-94.4% among the five cross-genera species of kelampayan. The present study is the first report of the development of EST-SSR markers in kelampayan. These markers will be valuable genomic resources that could pave the way for exploiting the genotype data for comparative genome mapping, association genetics, population genetics studies and molecular breeding of kelampayan and other indigenous tropical tree species in future.